Cognitive subtypes of probable Alzheimer's disease robustly identified in four cohorts - Scheltens, Nienke M. E.; Tijms, Betty M.; Koene, Teddy; Barkhof, Frederik; Teunissen, Charlotte E.; Wolfsgruber, Steffen; Wagner, Michael; Kornhuber, Johannes; Peters, Oliver; Cohn-Sheehy, Brendan I.; Rabinovici, Gil D.; Miller, Bruce L.; et al. (Alzheimers & Dementia, 2017)
INTRODUCTION: Patients with Alzheimer's disease (AD) show heterogeneity in profile of cognitive impairment. We aimed to identify cognitive subtypes in four large AD cohorts using a data-driven clustering approach. METHODS: We included probable AD dementia patients from the Amsterdam Dementia Cohort (n = 496), Alzheimer's Disease Neuroimaging Initiative (n = 376), German Dementia Competence Network (n = 521), and University of California, San Francisco (n = 589). Neuropsychological data were clustered using nonnegative matrix factorization. We explored clinical and neurobiological characteristics of identified clusters. RESULTS: In each cohort, a two-clusters solution best fitted the data (cophenetic correlation >0.9): one cluster was memory-impaired and the other relatively memory spared. Pooled analyses showed that the memory-spared clusters (29%-52% of patients) were younger, more often apolipoprotein E (APOE) ɛ4 negative, and had more severe posterior atrophy compared with the memory-impaired clusters (all P < .05). CONCLUSIONS: We could identify two robust cognitive clusters in four independent large cohorts with distinct clinical characteristics.
EVALuna2:33493